Dari Kerja Sama Transaksional Menuju Ekosistem Kolaboratif: Transformasi Manajemen Kemitraan dalam Menghadapi Disrupsi Digital - Lina Yunita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Digital disruption has transformed partnership management from bilateral arrangements focused primarily on transaction efficiency into collaborative ecosystems involving multiple actors, digital technologies, data resources, and diverse stakeholder interests. This transformation requires organizations to move beyond partner selection and contractual control toward orchestrating complementarities, fostering trust, governing data access, aligning incentives, and developing adaptive capabilities across organizational boundaries. This study aims to synthesize the literature on partnership management transformation in the context of digital disruption and to develop an integrative conceptual framework. A systematic literature review was conducted following the PRISMA 2020 guidelines. The review examined peer-reviewed journal articles published between 2015 and 2026 addressing strategic partnerships, business ecosystems, digital platforms, ecosystem governance, collaboration, orchestration, and digital transformation. Relevant studies were selected based on conceptual relevance, methodological rigor, publication quality, and their contributions to interorganizational governance and value creation. The findings reveal six major themes shaping digital partnership transformation: changes in relationship architecture, hybrid governance mechanisms, platform- and data-driven orchestration, strengthened relational mechanisms, the development of dynamic capabilities, and broader performance outcomes including innovation, organizational resilience, and sustainability. Based on these findings, this study proposes the Digital Ecosystem Partnership Transformation Framework, which integrates disruption pressures, relational-digital readiness, orchestration mechanisms, collaboration quality, and ecosystem performance into a comprehensive model. The study concludes that successful digital partnerships cannot rely solely on contractual arrangements or platform dominance. Instead, long-term partnership performance depends on modular organizational architecture, transparent governance, data interoperability, equitable value distribution, and the capability to continuously reconfigure interorganizational relationships in response to technological advancement and changing market conditions.